2011
DOI: 10.1002/jccs.201190016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biginelli Compounds Using Cobalt Hydrogen Sulfate

Abstract: Efficient synthesis of various 2-oxo(thioxo)-1,2,3,4-tetrahydropyrimidines containing acetyl, carboethoxy, carbomethoxy and carboxamide groups on 5-position of the N1-substituted and N1-unsubstituted heterocyclic ring was achieved using cobalt hydrogen sulfate Co(HSO 4 ) 2 under thermal conditions. Good to high yield, shorter reaction times, easy work up and simple preparation of Co(HSO 4 ) 2 are the advantages using this synthetic method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The increase of the required irradiation time in the presence of oxygen and also a failure of total quenching under oxygen are supporting the argument that both excited singlet and triplet states of THPMs are involved in the reaction as we also observed by irradiation in CHCl 3 solution [29,30]. The removal of 3-and 4-hydrogens in this study, namely photo-oxidation of THPMs in acetonitrile solution, is probably a result of homolytic cleavage of both C-H and N-H bonds.…”
Section: Photo-oxidationsupporting
confidence: 84%
See 1 more Smart Citation
“…The increase of the required irradiation time in the presence of oxygen and also a failure of total quenching under oxygen are supporting the argument that both excited singlet and triplet states of THPMs are involved in the reaction as we also observed by irradiation in CHCl 3 solution [29,30]. The removal of 3-and 4-hydrogens in this study, namely photo-oxidation of THPMs in acetonitrile solution, is probably a result of homolytic cleavage of both C-H and N-H bonds.…”
Section: Photo-oxidationsupporting
confidence: 84%
“…The title compounds were prepared through a three components condensation using Co(HSO 4 ) 2 [30]. Melting points were determined on a Stuart Scientific SMP2 apparatus and are uncorrected.…”
Section: Methodsmentioning
confidence: 99%
“…Cobalt hydrogen sulfate Co(HSO 4 ) 2 was prepared according to the method of Memarian et al [18] Polyphosphate ester was synthesized using the procedure reported by Kappe and his colleagues. [19] …”
Section: Synthesis Of the Lewis Acid Catalystsmentioning
confidence: 99%
“…[1][2][3] Therefore, because of their importance various works are devoted to the synthesis of these nitrogen containing heterocyclic compounds. [4][5][6] In our previous studies, we were interested in elucidating the parameters affecting the rate of thermal and photochemical oxidation of some nitrogen containing heterocyclic compounds, e.g. 1,4-dihydropyridines (DHPs), [7] 2-oxo-1,2,3,4-tetrahydropyrimidines (THPMs) [8] and 2,3-dihydroquinazolinones (DHQZs).…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahydropyrimidinone (THPMs) derivatives previously known as 3,4‐dihydropyimidine‐2‐( 1H )‐ones (DHPMs) exhibit a wide range of biological activities and pharmaceutical properties . Therefore, because of their importance various works are devoted to the synthesis of these nitrogen containing heterocyclic compounds . In our previous studies, we were interested in elucidating the parameters affecting the rate of thermal and photochemical oxidation of some nitrogen containing heterocyclic compounds, e.g.…”
Section: Introductionmentioning
confidence: 99%